0
$\begingroup$

This is my solution but I couldn’t find $h$ in term of $V \rightarrow M_{1} V - M_{2} V = M_{2} V_{2} \implies V \left( M_{1} - M_{2} \right) = M_{2} V_{2} \implies \frac{M_{1}}{M_{2}} = 1 + \frac{V_{2}}{V}$ and $V = V_{2} - V$ so $V_{2} = 2 V$ $\frac{M_{1}}{M_{2}} = 3$ if we apply Energy conservation $3 g h + \frac{3}{2} V^{2} + g h + \frac{1}{2} V^{2} = \frac{1}{2} 4 V^{2}$ (I think there is a mistake at the end)

enter image description here

$\endgroup$
1
  • 1
    $\begingroup$ Hello Ryuga and welcome to Physics SE. You provide very limited information on your problem. You don't declare the meaning of the variables and there is no information on the motivation behind your approach. I suggest you edit your question to provide some more information. This will greatly help people to provide some solution and/or insight on your problem. $\endgroup$
    – ZaellixA
    May 14 at 7:22

0

Browse other questions tagged or ask your own question.